Quality of life of children with epilepsy (neuropsychiatric and social aspects) - O. V. Guzeva (Učenye Zapiski Sankt-Peterburgskogo Gosudarstvennogo Medicinskogo Universiteta im. Akad. I.P. Pavlova, 2016)
Epilepsy is one of the most common neurological diseases in childhood and adolescence. It is on the third place in the structure of diseases of the nervous system. The social significance of this disease is determined by the highest percentage in disability of patients. Currently, many leading national and foreign epileptologists expresses the same opinion that the one of the most important purposes in helping patients with epilepsy is to improve their quality of life. Cognitive disorders play a leading role in disturbances of patients’ adaptation in the community, so their role can be more considerable in disability than seizures, thus impairing the quality of life. The most common cognitive disorders in patients with epilepsy include memory impairment, retarded intellectual development and attention deficit disorder. In recent years, a special interest is given to the introduction of neuropsychological methods in studying the brain organization of higher mental functions in children with epilepsy. Analysis of neuropsychological features and characteristics of cognitive disorders with various forms of idiopathic epilepsy is of particular interest.